The Proteolytic Regulation of Virus Cell Entry by Furin and Other Proprotein Convertases - Izaguirre, Gonzalo (Viruses, 2019)
A wide variety of viruses exploit furin and other proprotein convertases (PCs) of the constitutive protein secretion pathway in order to regulate their cell entry mechanism and infectivity. Surface proteins of enveloped, as well as non-enveloped, viruses become processed by these proteases intracellularly during morphogenesis or extracellularly after egress and during entry in order to produce mature virions activated for infection. Although viruses also take advantage of other proteases, it is when some viruses become reactive with PCs that they may develop high pathogenicity. Besides reacting with furin, some viruses may also react with the PCs of the other specificity group constituted by PC4/PC5/PACE4/PC7. The targeting of PCs for inhibition may result in a useful strategy to treat infections with some highly pathogenic viruses. A wide variety of PC inhibitors have been developed and tested for their antiviral activity in cell-based assays.